A magnetic nanoparticle-supported N-heterocyclic carbene-palladacycle: an efficient and recyclable solid molecular catalyst for Suzuki–Miyaura cross-coupling of 9-chloroacridine. Issue 97 (22nd November 2017) - Deng, Qinyue; Shen, Yajing; Zhu, Haibo; Tu, Tao
Abstract : A robust magnetic nanoparticle-supported NHC-palladacycle functioned as a recyclable solid molecular catalyst and exhibited high catalytic activity towards the challenging Suzuki–Miyaura cross-coupling of 9-chloroacridines. Abstract : A robust magnetic nanoparticle-supported N-heterocyclic carbene-palladacycle has been readily synthesized by directly anchoring the structural defined acenaphthoimidazolylidene palladacycle with a long tail on magnetic nanoparticles (MNPs), and functioned as a solid molecular catalyst and exhibited extremely high catalytic activity towards the challenging Suzuki–Miyaura cross-coupling reactions between less-studied heterocyclic 9-chloroacridine and diverse boronic acids. Remarkably, the catalyst could be used 5 times without obvious loss of activity highlighting the efficiency of our strategy of immobilization of previledged catalysts.